PENINGKATAN KOMPETENSI PEDAGOGIK DAN PROFESIONAL GURU DALAM PEMBELAJARAN DARING PADA MASA PANDEMI DI MI AS-SALAM KOTA BATU - Ari Kusumawati; Mohammad Afifulloh; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
In the learning process, teacher competencies must be implemented optimally, especially in mastering pedagogic and professional competencies. Mastery of these two competencies is considered very important for teachers because these competencies are very inherent in learning. This research was conducted at MI As-Salam Batu City. This research uses descriptive qualitative research with the type of case study research. Based on the research that has been done, the pedagogical and professional competence of MI As-Salam teachers has increased. This is evidenced by the increase in teacher resources before and after the pandemic. Kata kunci: Kompetensi guru, kompetensi pedagogik, kompetensi profesional guru, pembelajaran daring